Practices and Challenges: Riau Islands EFL Teachers’ View on Differentiated Instructions in Kurikulum Merdeka - Theodesia Lady Pratiwi; Nurhayati Balqis; Pandu Prasodjo (Universitas Islam Negeri Madura, 2026)
Kurikulum Merdeka has been implemented since 2020; one of its characteristics is the implementation of differentiated instruction. Differentiated instruction is an old strategy; however, it is a quite new strategy for most current teachers in Indonesia. Thus, this study aims to examine the perceptions of high school English teachers in the Riau Islands regarding the implementation of differentiated instruction within the Kurikulum Merdeka framework. This study employed a mixed-methods research approach, combining quantitative and qualitative data. The research instruments are a questionnaire and an interview to get a deeper analysis. This study found that EFL teachers in Riau Islands Province showed positive perceptions of the implementation of differentiated instruction. The teachers also admitted the importance of adapting to students’ diverse needs, abilities, and learning styles. However, the teachers also face several challenges during the implementation of differentiated instruction, such as limited time and resources to prepare, as well as difficulties in adapting the instruction to large class sizes. Despite those challenges, EFL teachers still perceive the usefulness and effectiveness of differentiated instruction to develop English language skills. In a nutshell, differentiated instruction can significantly improve the learning outcomes, but adequate professional training and resources are necessary for better implementation.